Upstream motion of chorus wave generation: comparisons with observations - Foster, John C.; Erickson, Philip J.; Omura, Yoshiharu (Frontiers in Astronomy and Space Sciences, 2024)
An understanding of the development of strong VLF chorus elements is important in the study of the rapid MeV electron acceleration observed during radiation belt recovery events. Foster et al. [2021] described chorus elements with long-duration (20-40 ms), strong (|Bw| 0.5 -2.0 nT) subpackets with smoothly varying frequency and phase capable of producing nonlinear energy gain of 1-2% for multi-MeV seed electrons. For such strong chorus elements, we examine the consequences of an upstream motion of the chorus wave generation region using Van Allen Probes observations and nonlinear theory. For a given upstream velocity, vs, resonant electron energy (50-350 keV) and pitch angle (105-115 deg) are uniquely determined for each wave frequency. We examine the effect of an upstream vs on the inhomogeneity factor that controls wave growth. For steadily increasing upstream motion as the chorus element evolves, vs/c ranging over [-0.001, -0.065], nonlinear wave growth takes place at ≥ 50% of the theoretical maximal value during the development of the observed strong subpackets. For the cases examined, resonant electron energies and pitch angles closely match those of the observed injected electron flux enhancements responsible for chorus development and the nonlinear acceleration of MeV radiation belt electrons.